PROFESSIONAL DEVELOPMENT OF TEACHER EDUCATORS OF BASIC EDUCATION TEACHERS IN A TRAINING CENTER IN MATO GROSSO - MARLI ELIZA DALMAZO AFONSO DE ANDRE; Sívia Matsuoka (Editora da Universidade de Santa Cruz do Sul, 2016)
This paper presents data from a study that investigated the professional development of teacher educators who work in the Training Centre for Basic Education Professionals (Cefapro) in the state of Mato Grosso. They are responsible for the implementation of continuing education in schools. The methodological procedures included a survey with all teacher educators (PF), focus group with five PFs and systematic observation of the performance of a PF. The theoretical framework was based on studies of authors such as Carlos Marcelo (1992; 1996; 1999; 2009), Jacky Beillerot (1996) and Marguerite Altet (2003). The analysis focused on the relationship between Teacher educators and their functions, those prescribed by the Training Policy, as well as those determined by the training needs of teachers in school, understanding that this relationship guides the development of professionalism of this new educational actor.